TINDAK TUTUR ILOKUSI PADA PIDATO KENEGARAAN PRESIDEN JOKOWI TANGGAL 14 AGUSTUS 2015 - Ramanda, Arnola Dwika; Ermanto, Ermanto; Juita, Novia (Universitas Negeri Padang, 2017)
This study aimed to describe the Speech Acts illocutionary At the State Address of President Jokowi Date August 14, 2015.This study is a qualitative study using descriptive methods. The main data in this study are speech-speech on a speech by President Jokowi containing illocutionary speech acts on the President's speech Jokowi dated August 14, 2015. The source of this research data is video of President Jokowi first official speech on August 14, 2015, which is downloaded via youtube. The instrument of this study is the researchers themselves. Data collected by the state address how to download video youtube President Jokowi through, listening to the speech of President Jokowi, President Jokowi and transcribe speech into written language.Examination of the validity of the data was done by using trilingulasi. Data analysis was done by (1) transcribe the recording data in written language, (2) classified based on the type of follow illocutionary speech, speech acts function, and the strategy says, in a speech by President Jokowi dated August 14, 2015, (3) analyzing the data that have been classified, (4) make the conclusion of the research results Based on data from this study, it was found 94 research data, the type of representative illocutionary speech act, directive, expressive, commissive, declaration. Illocutionary speech acts function is the function that is found fun and work. Bertutur strategy used strategy spoken directly without further ado, strategy speak frankly with the preamble of positive politeness, and strategies speak frankly with the preamble of negative politenessKeywords:Speech Acts, Presidential Speech